Spatial variability of water electrical conductivity in underground dam areas in the semi-arid region of Rio Grande do Norte, Brazil - Chianca, Cibele Gouveia Costa (2023)
Underground dams have been widely deployed in the semi-arid region of Rio Grande do Norte, a state in the Brazilian Northeast, aiming to mitigate the effects caused by water scarcity. In this study, the geographic distribution of the electrical conductivity of water of underground dams was evaluated at the end of the dry season of 2018 and at the end of the rainy season of 2019. Maps were created in ArcGIS 10.4.1 software using the Inverse Distance Weighted interpolator. The results indicated high electrical conductivity variability in the evaluated underground dams. The highest values were obtained in the eastern portion of the Rio Grande do Norte state, except for two dams, located in the municipalities of Apodi and Severiano Melo. In most of the underground dams (64%), the water has an electrical conductivity with low soil salinization potential (EC < 0.7 dS m-1). It was observed that the salinity of the underground dams is influenced by several factors, such as climate, relief, land use and occupation due to rural agglomerations and animal husbandry in the dam hydrographic basin, and intensive nutritional management with fertilizers in the dam area.